2003
DOI: 10.1074/jbc.m210847200
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Phospholipid Transfer Protein (PLTP) and PLTP-generated Pre-β-high Density Lipoprotein by Mast Cell Chymase Impairs High Affinity Efflux of Cholesterol from Macrophage Foam Cells

Abstract: Human atherosclerotic lesions contain mast cells filled with the neutral protease chymase. Here we studied the effect of human chymase on (i) phospholipid transfer protein (PLTP)-mediated phospholipid (PL) transfer activity, and (ii) the ability of PLTP to generate pre-␤-high density lipoprotein (HDL). Immunoblot analysis of PLTP after incubation with chymase for 6 h revealed, in addition to the original 80-kDa band, four specific proteolytic fragments of PLTP with approximate molecular masses of 70, 52, 48, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
5
24
1
Order By: Relevance
“…6). These data, using a system in which ABCA1-dependent efflux dominates, confirmed that the ability of HDL 3 to stimulate cholesterol efflux from cholesterol-loaded macrophages is increased after PLTP treatment (39). More importantly, using HDL 3 preparations with graded pre-␤ content it could be demonstrated that the rate of cholesterol efflux from the cells varied in parallel with the content of pre-␤ particles in HDL 3 (Fig.…”
Section: Influence Of the Content Of Pre-␤-hdl On The Hdl 3 -Promotedsupporting
confidence: 67%
See 2 more Smart Citations
“…6). These data, using a system in which ABCA1-dependent efflux dominates, confirmed that the ability of HDL 3 to stimulate cholesterol efflux from cholesterol-loaded macrophages is increased after PLTP treatment (39). More importantly, using HDL 3 preparations with graded pre-␤ content it could be demonstrated that the rate of cholesterol efflux from the cells varied in parallel with the content of pre-␤ particles in HDL 3 (Fig.…”
Section: Influence Of the Content Of Pre-␤-hdl On The Hdl 3 -Promotedsupporting
confidence: 67%
“…To increase the content of pre-␤ particles, HDL 3 was preincubated for 24 h at 37°C in buffer alone or with PLTP, demonstrated previously to promote the size conversion of HDL particles and to generate pre-␤-HDL (38). As reported previously (39), PLTP treatment of HDL 3 for 24 h increased the content of pre-␤-HDL in the HDL 3 preparation (in this experiment from 9 to 18%; Fig. 5, A and B, left).…”
Section: Influence Of the Content Of Pre-␤-hdl On The Hdl 3 -Promotedsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, studies in vitro have demonstrated that chymase specifically depletes preb-HDL particles (26), thus blocking cholesterol efflux mediated by the ABCA1 pathway (27). In contrast, limited proteolysis of HDL 3 particles by chymase does not impair their ability to activate LCAT (28) or to act as phospholipid acceptors in PLTP-mediated phospholipid transfer reactions (29). These observations reveal that the spherical a-HDL particles primarily remain functional even after being exposed to chymase.…”
mentioning
confidence: 60%
“…These observations reveal that the spherical a-HDL particles primarily remain functional even after being exposed to chymase. Chymase also degrades PLTP, thereby reducing its phospholipid transfer activity (29). However, it is not known whether chymase is able to degrade CETP, its structurally closely related lipid transfer protein.…”
mentioning
confidence: 99%